Peningkatan Manajemen Koleksi Skripsi Perpustakaan UPY menggunakan Sistem Informasi Berbasis Web Terintegrasi - Murniady Muchran; Ginanjar Setyo Nugroho; Gulam Hazmin; Adi Prasetyo (Universitas PGRI Yogyakarta, 2023)
The library information system created at Universitas PGRI Yogyakarta (UPY) plays an important role in managing and organizing diverse library collections. Its goal is to provide efficient services to users, whether students, lecturers, or researchers, so that they can easily access and utilize available information sources. By using the library information system, library managers can manage the inventory of library collections more efficiently. They can monitor and update information about books, theses, dissertations, and scientific articles owned by the library. This makes it easier for users to find and obtain relevant information sources related to their study or research topics. Overall, the UPY library information system is an efficient and effective solution for managing library collections and providing better services to users. With this system, users can easily access the information sources they need, as well as improve the quality of research, study, and learning in the university environment.